Islamic Educational Values Contained In The Wedding Tradition Of The Sambas Malay Community - Ilham; Syahruddin Usman; Baharuddin; Purniadi Putra (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The purpose of this research is to analyze the values of Islamic education contained in the marriage tradition of the Sambas Malay community. This research uses a qualitative approach. The approach used in this research is a phenomenological approach. Data collection techniques with observation, interviews and documentation. Data analysis uses data collection, data reduction, data presentation and conclusion drawing. Primary data sources were obtained from cultural leaders, and religious leaders as key informants and several village heads and elements of implementing marriage activities. While secondary data is obtained from books, journals, and websites. The results showed that the wedding tradition of Sambas Malay community is based on the philosophy of